High-load bolt steel with self-passivation function, preparation process and application thereof

CN122898798APending Publication Date: 2026-10-13DONGGUAN JINFENG MOLD STEEL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611118194.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,此类方案仍侧重于通过成分均匀化与组织调控来改善材料本征性能,其耐腐蚀性的提升本质上源于基体均匀的合金化,并未改变均匀材料与被动防护的传统范式,在极端腐蚀环境中长效服役的可靠性仍面临挑战

Benefits of technology

[0055](1)本发明提供的具有自钝化功能的高荷载螺栓钢,通过梯度结构+核壳颗粒+网络分布的多层级设计,实现了材料在超高强度、本征长效耐蚀性与主动修复能力方面的协同跨越,提高材料在极端工况下材料构件的承载安全性与环境耐受性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898798A_ABST
    Figure CN122898798A_ABST
Patent Text Reader

Abstract

The application provides a high-load bolt steel with a self-passivation function, a preparation process and application of the bolt steel, and the bolt steel is a gradient composite rod or a forged blank, which is composed of a core matrix area and a near-surface functional composite area. The core matrix area is a high-strength and high-toughness tempered martensite / sorbite structure, which provides a main mechanical bearing network; 3-15 vol% of core-shell structure functional particles are dispersed in the near-surface functional composite area, the particles are elongated along the flow lines through thermal mechanical processing, and a chain / layer / intermittent network corrosion control network is formed. The network and the mechanical bearing network of the outer layer are three-dimensionally interpenetrated in the near-surface layer, forming a self-passivation-slow-release double network structure. The material simultaneously realizes a tensile strength of greater than or equal to 1200 MPa, excellent toughness and excellent corrosion resistance without relying on thick coatings, and is particularly suitable for key connections in extreme corrosion and high stress coupling environments such as marine engineering, new energy equipment, major infrastructure and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of advanced metal structural material preparation technology, specifically to a high-load bolt steel with self-passivation function, its preparation process, and its application. Background Technology

[0002] High-load bolts are core connectors in major equipment and critical infrastructure, widely used in marine engineering, cross-sea bridges, wind power generation, nuclear power facilities, and petrochemical industries. Their performance directly affects the safety and service life of the overall structure. As equipment develops towards larger size, higher parameters, and extreme environments, stringent requirements are placed on bolt steel for both ultra-high strength and excellent corrosion resistance.

[0003] Patent CN202311613143.5 discloses a high-strength bolt steel material resistant to delayed fracture and a bolt manufacturing method, aiming to improve the material's resistance to hydrogen-induced cracking by optimizing alloy composition and heat treatment process. However, such solutions still focus on improving the intrinsic properties of the material through composition homogenization and microstructure regulation. The improvement in corrosion resistance essentially stems from the homogenization of the matrix, without changing the traditional paradigm of homogeneous materials and passive protection. The reliability of long-term service in extreme corrosive environments still faces challenges.

[0004] To address the aforementioned problems, this invention proposes a high-load bolt steel with self-passivation function, its manufacturing process, and its application. Through gradient composite design and the introduction of core-shell structured functional particles, a three-dimensional, interpenetrating, and functionally differentiated intrinsic protection system is actively constructed near the material's surface. This system spatially decouples and integrates mechanical load-bearing and corrosion control functions, enabling the bolt steel to simultaneously achieve ultra-high strength exceeding 1200 MPa and long-lasting, active corrosion protection capabilities without any thick coating. Summary of the Invention

[0005] To address existing technical problems, this invention provides high-load bolt steel with self-passivation function, its preparation process, and its applications. This high-load bolt steel, through a unique gradient composite design and the introduction of core-shell functional particles, constructs a dual-network system within the material, consisting of a three-dimensional interpenetrating mechanical load-bearing network and a corrosion control network. The mechanical load-bearing network, composed of a core matrix region and a continuous steel skeleton, provides ultra-high strength (≥1200 MPa) and excellent toughness. The corrosion control network is composed of chain / network distribution of core-shell functional particles elongated along the streamlines near the surface, achieving self-passivation through a Cr-rich outer functional layer and slow-release repair through a Cu-based core. The two networks are synergistically coupled within the near-surface depth range, achieving spatial division of labor and performance unification of mechanical load-bearing and active corrosion protection functions. This can meet the harsh working conditions with extreme requirements for safety and reliability, such as the high salt spray corrosion environment of marine engineering and offshore wind power, long-term protection of bridge cables and anchoring systems, high-stress connections of energy and power facilities under corrosive media, and core fastening nodes in high-end equipment that are difficult to maintain repeatedly.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] This invention provides a high-load bolt steel with self-passivation function. The bolt steel is a gradient composite bar or forging billet, divided radially from the inside to the outside into:

[0008] The cardiac basal region, and the near-surface functional complex surrounding the cardiac basal region, including:

[0009] The tensile strength Rm of the core matrix region is ≥1200 MPa. The core matrix region is formed by matrix steel, and its microstructure is mainly tempered martensite or tempered sorbite. The matrix steel contains, by weight percentage: C 0.25%-0.38%, Si 0.10%-0.50%, Mn 0.50%-1.20%, Cr 0.70%-1.50%, Mo 0.15%-0.50%, Ni 0.80%-2.50%, with the balance being Fe and unavoidable impurities.

[0010] The near-surface functional composite zone is set within a depth range of 0.3-2.0 mm on the outer surface of the bolt steel, and is composed of a continuous steel skeleton made of matrix steel and functional particles dispersed within the skeleton.

[0011] The functional particles have a volume fraction of 3-15 vol% in the near-surface functional composite region and possess a core-shell structure, wherein: the core is composed of Cu or a Cu-based alloy, and the shell is a composite shell layer covering the core, comprising at least the following layers arranged sequentially from the inside out:

[0012] A diffusion barrier layer, the material of which is one or more of Al2O3, Y2O3 or TiC;

[0013] The outer functional layer is made of Cr-rich alloy or Cr-rich-Mo alloy, wherein the Cr content is ≥15 wt%.

[0014] Functional particles are elongated along the forging / rolling flow line in the near-surface functional composite zone, with an aspect ratio greater than 2:1, forming a chain-like / lamellar / discontinuous network distribution, constituting a corrosion control network. The corrosion control network is nested within a continuous steel skeleton, and the two form a three-dimensional interpenetrating self-passivation-slow-release dual-network structure in the near-surface functional composite zone.

[0015] This application does not use traditional steel with uniform composition and microstructure, but rather a composite structure designed with a radial gradient distribution:

[0016] The core matrix region, as the main load-bearing skeleton of the material, bears most of the tensile, shear, and fatigue loads of the bolts. The near-surface functional composite region, as the active protective shell of the material, is the primary battleground for corrosion and a sensitive area for stress corrosion. Without significantly compromising the strength and toughness of the matrix, it endows the material with intrinsic, actively responsive corrosion resistance.

[0017] The cores of the core-shell particles in the near-surface functional composite zone can undergo selective dissolution at the corrosion potential, releasing Cu. + / Cu 2+ Ions. After these ions migrate to the active anodic region where the passivation film is damaged, they can effectively inhibit the further development of localized corrosion through chemical / electrochemical interactions, achieving slow-release repair.

[0018] The diffusion barrier layer prevents interdiffusion between the Cu core and the Fe matrix during subsequent high-temperature hot isostatic pressing and heat treatment, avoiding the formation of low-melting-point eutectic phases or brittle intermetallic compounds, thereby ensuring the integrity of the particle structure and functional independence.

[0019] The outer functional layer is rich in high concentrations of Cr, and can rapidly form a dense, stable, and Cr-rich layer in corrosive media. 2 O 3 The passivation film significantly increases the corrosion potential and pitting resistance of the material, achieving self-passivation.

[0020] Through a specific forging process, the functional particles near the surface are elongated and connected along the metal rheological direction. This distribution pattern ensures that channels rich in passivating and slow-release elements form a quasi-continuous network in the near-surface layer of the material. When scratches or pitting occur on the surface, the corrosive medium cannot easily bypass this network to directly attack the vulnerable core matrix, but must first interact with the network. The network can respond rapidly, mobilizing its self-passivation and slow-release functions at the point of damage, thereby suppressing localized corrosion in its nascent stage.

[0021] In some embodiments, the base steel further comprises one or more of the following elements: V 0.05%–0.15%, Nb 0.02%–0.10%, and B 0.0005%–0.0035%.

[0022] This application achieves comprehensive optimization of the microstructure, toughness, and hardenability of the matrix steel through the synergistic design and precise control of microalloying elements V, Nb, and B. It can optimize the toughness and microstructure uniformity of the matrix while ensuring its ultra-high strength, providing a strong, tough, and stable supporting matrix for the near-surface functional composite zone. The specific mechanism is as follows:

[0023] The added Nb forms a fine, stable Nb(C,N) phase with the C and N in the steel. During the reheating and forging process, these precipitated phases effectively pin austenite grain boundaries and dislocations, inhibit grain growth, and further refine the microstructure through strain-induced precipitation. This ultimately results in finer proto-austenite grains, which then transform into smaller martensite laths / blocks, providing the material with higher toughness and a lower tendency for brittle fracture, while also improving microstructure uniformity.

[0024] Trace amounts of boron preferentially segregate at austenite grain boundaries during cooling, effectively suppressing the nucleation and growth of soft phases such as proeutectoid ferrite and granular bainite along these grain boundaries. This significantly improves the hardenability of the material, especially under conditions of large cross-sections or uneven cooling, ensuring that the core structure remains predominantly martensite and preventing the deterioration of mechanical properties and corrosion resistance caused by the formation of soft phase channels.

[0025] The added V element helps refine the grains at high temperatures and precipitates nanoscale, coherent / semi-coherent VC / V (C, N) particles in the martensitic / tempered sorbite matrix during tempering. These precipitates produce a significant secondary precipitation strengthening effect, thereby further improving the strength of the material without increasing the carbon content, and avoiding the risks of carbide network precipitation and intergranular embrittlement caused by high carbon content.

[0026] In some implementations, the core matrix region satisfies one or more of the following conditions:

[0027] I. C content is 0.27%–0.33%, Cr content is 0.90%–1.20%, Mo content is 0.20%–0.40%, and Ni content is 1.20%–1.80%;

[0028] II. Grain size ≥ grade 8;

[0029] III. Tensile strength Rm is 1250-1350 MPa, and yield strength Rp0.2 is ≥1100 MPa.

[0030] In some implementations, the overall equivalent diameter of the functional particles, D90, is ≤80μm, and the functional particles are distributed in a discontinuous network-like permeation tendency within the near-surface functional composite zone.

[0031] This application controls the size of functional particles within the matrix by limiting their overall equivalent diameter, and through a specific forging process, elongates and aligns the particles along the metal rheological direction, forming a spatially quasi-continuous but physically incompletely dense network. This distribution pattern ensures that the propagation path of the corrosive medium near the surface must repeatedly interact with the particle network rich in passivating and slow-release elements, thereby maximizing the network's interception and response efficiency.

[0032] In some embodiments, the core of the functional particle is a Cu-Ni alloy, Cu-Sn alloy, or Cu-Ni-Sn alloy, wherein the total content of Ni and Sn is ≤15 wt%.

[0033] This application defines the core composition and specific metal content, with Cu being the core element providing the sustained-release repair function. The addition of appropriate amounts of Ni and Sn aims to improve the strength and thermal stability of the core alloy and regulate its electrode potential, preventing excessive deformation or harmful interfacial reactions with the matrix due to excessive core softness during subsequent hot isostatic pressing and heat treatment. Limiting the total amount of alloying elements ensures that the core remains predominantly Cu, maintaining sufficient controllable dissolution capacity and providing effective Cu... 2+ Ion source.

[0034] In some embodiments, the thickness of the diffusion barrier layer is 0.1-2.0 μm, the thickness of the outer functional layer is 0.3-2.0 μm, and the content of Cr in the outer functional layer is 15-30 wt%, and the content of Mo is 1-5 wt%.

[0035] In some embodiments, the outer functional layer comprises Fe-Cr or Fe-Cr-Mo, wherein Cr is 15-30 wt% and Mo is 1-5 wt%, and is metallurgically bonded to the base steel in a nanocrystalline / microcrystalline morphology.

[0036] This application defines the composition and thickness of the diffusion barrier layer and the outer functional layer. The core function of the diffusion barrier layer is to effectively block atomic interdiffusion between the Cu core and the Fe matrix during high-temperature consolidation and heat treatment, preventing the formation of low-melting-point eutectics or brittle intermetallic compounds, thereby maintaining the integrity of the core-shell structure and ensuring the independent function of the core. The high Cr content in the outer functional layer ensures the rapid formation of a stable, dense, and Cr-rich layer in corrosive media. 2 O 3 The passivation film significantly increases the corrosion potential. The addition of Mo further enhances the stability of the passivation film, especially in materials containing Cl. -Resistance to pitting corrosion and repassivation rate in the environment. The outer functional layer, with its nanocrystalline / microcrystalline structure and metallurgical bonding, ensures that it is not easily peeled off under stress.

[0037] Existing technologies typically combine a high-strength, high-toughness substrate with an external protective coating to enhance the strength and corrosion resistance of high-strength bolts. The substrate achieves high strength through optimized alloy composition and heat treatment processes, while corrosion resistance is achieved through external coatings such as electroplating or Dacromet coating. This approach has inherent drawbacks: First, the coating is prone to localized damage under assembly stress, wear, or environmental erosion, forming a small anode-large cathode corrosion cell that accelerates localized corrosion and stress corrosion cracking of the substrate, posing a risk of sudden failure in protective reliability. Second, the increased carbon equivalent required to achieve high strength and the coating process applied to improve corrosion resistance often conflict, potentially leading to increased hydrogen embrittlement risk, compromised substrate toughness, and systemic problems such as complex friction coefficient control and high life-cycle maintenance costs.

[0038] To address the aforementioned issues, this application utilizes core-shell functional particles dispersed throughout the matrix, connected along the processing flow lines to form a chain-like / lamellar / discontinuous network distribution. The chromium-rich (molybdenum) outer functional layer provides rapid self-passivation, while the copper-based core acts as a slow-release ion source, inhibiting corrosion propagation when the passivation film is damaged. This design decouples and integrates the high-strength matrix and active corrosion protection within the material: the core can focus on mechanical load-bearing capacity, while the near-surface functional network provides intrinsic and long-lasting corrosion protection. This reduces the risk of sudden corrosion caused by coating damage, avoids the damage to the matrix's toughness caused by traditional protective processes, and simultaneously endows bolts with excellent durability and reliability under extreme corrosion and high-stress coupling environments.

[0039] A second aspect of this invention provides a process for preparing high-load bolt steel with self-passivation function.

[0040] Includes the following steps:

[0041] (1) Raw material preparation: Provide matrix steel powder and core-shell structured functional particles;

[0042] (2) Gradient powder loading and encapsulation: Within the low-carbon steel casing, a near-surface powder loading zone is formed by a mixture of matrix steel powder and 3-15 vol% functional particles, while a core powder loading zone is formed by pure matrix steel powder; the mixture is then degassed at 400-450℃, followed by heating at 350-500℃ and vacuuming to ≤10 -2 After sealing (Pa);

[0043] (3) Hot isostatic pressing (HIP) densification: Hold pressure at 1090-1120℃ and 100-120 MPa for 2-5 h, then cool to obtain a fully dense gradient composite preform;

[0044] (4) Thermomechanical deformation: The gradient composite billet is heated to 1080-1140℃ and held at that temperature. After holding at that temperature with an effective cross section of 0.6-1.2 min / mm, it is forged. At least two passes of deformation are carried out in the temperature range of 850-960℃, with a single pass reduction of 15-30%, a cumulative true strain ≥0.6, and a final forging temperature ≥820℃. After forging, it is slowly cooled or the hot billet is put into the furnace.

[0045] (5) Heat treatment: Austenitizing quenching and tempering are performed in sequence; the austenitizing quenching temperature is 860-900℃, and the holding time is 2-5 h; the tempering temperature is 480-520℃, and the holding time is 2-5 h, followed by air cooling or water cooling.

[0046] (6) Machining and surface treatment: Turn / grind to bolt size, roll forming of threads, low temperature stabilization: 150-220℃×1-3 h dehydrogenation baking, phosphating or chromium-free passivation treatment of the surface to obtain finished bolts / studs / anchors;

[0047] (7) Inspection: Magnetic particle testing or eddy current testing is performed on the root of the finished thread to remove unqualified products.

[0048] In some embodiments, in step (1), the core-shell functional particles are prepared by a method comprising the following steps:

[0049] (a) Provide Cu-based alloy core powder with a particle size D50 of 20-80 μm;

[0050] (b) An Al2O3 or Y2O3 diffusion barrier layer with a thickness of 0.2-1.5 μm is formed on the surface of the core powder using the sol-gel method or chemical vapor deposition method;

[0051] (c) An Fe-Cr-Mo alloy external functional layer with a thickness of 0.3-2.0 μm is deposited on the surface of the diffusion barrier layer by magnetron sputtering or fluidized bed chemical vapor deposition, wherein the Cr content is 15-30 wt% and the Mo content is 1-5 wt%.

[0052] (d) The coated powder is heat-treated at 400-600℃ for 0.5-2 hours in an inert or vacuum atmosphere to obtain functional particles.

[0053] A third aspect of the present invention provides a high-load fastener, which is manufactured from the aforementioned high-load bolt steel and has a nominal tensile strength grade ≥10.9.

[0054] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0055] (1) The high-load bolt steel with self-passivation function provided by the present invention achieves a synergistic leap in the material in terms of ultra-high strength, intrinsic long-term corrosion resistance and active repair capability through a multi-level design of gradient structure + core-shell particles + network distribution, thereby improving the load-bearing safety and environmental tolerance of the material components under extreme working conditions.

[0056] (2) This invention achieves intrinsic decoupling and efficient integration of mechanical load-bearing and corrosion protection functions within the material through a gradient multilayer structure design of the core matrix region and the near-surface functional composite region. The core matrix can focus on obtaining ultra-high strength and toughness through optimized alloy composition and heat treatment processes, while the near-surface functional composite region is dedicated to corrosion protection. The two are metallurgically bonded and mechanically connected through a continuous steel skeleton. This structure allows the material to form a complete load-bearing-protection integrated system within its matrix itself without relying on any thick outer coating, thereby eliminating the risk of sudden corrosion failure caused by coating damage.

[0057] (3) This invention constructs a self-passivation-slow-release dual-network structure in the near-surface functional composite zone, formed by the directional distribution of functional particles along the processing flow line. This corrosion control network is interconnected with the steel skeleton in three-dimensional space, which not only physically blocks the rapid expansion channel of the corrosive medium, but also endows the material with intelligent behavior of actively responding to corrosion invasion. Among them, the Cr (Mo)-rich outer functional layer network provides immediate and stable self-passivation capability, while the connecting path formed by the Cu-based core acts as a slow-release ion source, which can selectively dissolve when the passivation film is locally damaged, inhibiting corrosion development and realizing the "self-repair" of the material, thereby significantly improving its resistance to pitting corrosion, crevice corrosion and stress corrosion cracking.

[0058] (4) The functional particles designed in this invention have a core-shell structure, with each layer of components undertaking a specific function and working synergistically. The diffusion barrier layer composed of A2O3, Y2O3, etc., effectively isolates the harmful interdiffusion between the Cu core and the steel substrate in high-temperature processes, ensuring the independence of the core function; the Cr (Mo)-rich outer functional layer serves as a pre-seed for the passivation film, ensuring rapid film formation; and the Cu or Cu-based alloy core serves as a reliable slow-release ion pool. The network formed by these components ultimately achieves a qualitative change from passive protection to active control, significantly improving the service life and reliability of bolts in harsh corrosive environments. Attached Figure Description

[0059] Figure 1 This is a flowchart illustrating the preparation process of the high-load bolt steel with self-passivation function according to the present invention. Detailed Implementation

[0060] The present invention will be described below with reference to specific implementation schemes. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope. High-load bolt steel with self-passivating function is prepared according to the proportions and preparation methods of the raw materials specified in the following embodiments and comparative examples.

[0061] To facilitate the implementation of this invention by those skilled in the art, the following description is provided regarding the manufacturers of some raw materials used in the examples and comparative examples: the compounds and related reagents used are all commercially available.

[0062] Preparation Example 1

[0063] Preparation of thin-shell functional particles with Cu-Ni core / Al2O3 diffusion barrier / Fe-Cr-Mo outer functional layer:

[0064] Cu-5wt%Ni spherical alloy powder prepared by gas atomization was selected as the core, and its particle size D50 was controlled at 35±5μm.

[0065] The coating was performed using a sol-gel method. The core powder was immersed in a 0.1 mol / L aluminum isopropoxide solution in isopropanol and stirred continuously at 60°C for 2 hours.

[0066] After completion, the powder was collected by filtration, dried at 120°C for 2 hours, and then heat-treated at 550°C in air for 1 hour to completely convert the aluminum salt into Al2O3. The diffusion barrier layer formed in this process is approximately 0.5 μm thick.

[0067] Using an alloy with a composition of Fe-25wt%Cr-5wt%Mo as the target material, Al2O3-coated powder was placed in a fluidized bed sputtering apparatus under an argon atmosphere. The sputtering power was controlled at 1.5 kW, the substrate bias at -50 V, and the deposition time at 30 minutes. A uniform, dense Fe-Cr-Mo alloy external functional layer with a thickness of approximately 0.3 μm was deposited on the powder surface.

[0068] The deposited powder was annealed under vacuum at 450°C for 1 hour to eliminate internal stress, promote the bonding between the outer functional layer and the diffusion barrier layer, and stabilize the nanocrystalline structure to obtain functional particles.

[0069] Preparation Example 2

[0070] Preparation of thick-shell functional particles: Cu-Ni core / Al2O3 diffusion barrier layer / Fe-Cr-Mo outer functional layer:

[0071] Cu-5wt%Ni spherical alloy powder prepared by gas atomization was selected as the core, and its particle size D50 was controlled at 40±5μm.

[0072] Metal-organic chemical vapor deposition (MOCVD) was employed. Trimethylaluminum and oxygen were used as precursors to deposit fluidized core powder in a reaction chamber at 400°C for 40 minutes, forming a uniform, dense Al2O3 film with a thickness of approximately 1.0 μm as a diffusion barrier.

[0073] Using Fe-25Cr-5Mo target material, deposition was carried out at a higher power density of 3.0 kW and appropriate argon pressure, extending the deposition time to 180 minutes. The powder fluidization state needed to be controlled during the process to ensure coating uniformity, ultimately yielding an Fe-Cr-Mo alloy outer functional layer with a thickness of approximately 2.0 μm.

[0074] The deposited powder was annealed under vacuum at 450°C for 1 hour to eliminate internal stress, promote the bonding between the outer functional layer and the diffusion barrier layer, and stabilize the nanocrystalline structure to obtain functional particles.

[0075] Preparation Example 3

[0076] Preparation of functionalized particles: Cu-Sn core / Y2O3 diffusion barrier layer / Fe-Cr outer functional layer:

[0077] Cu-3wt%Sn spherical alloy powder was prepared by gas atomization, with the particle size D50 controlled within 30 ± 5 μm. The powder was ultrasonically cleaned with acetone and ethanol and then dried before use.

[0078] Using yttrium nitrate and citric acid as precursors, a stable sol is formed by dissolving in deionized water.

[0079] The core powder was added to the sol and stirred continuously at 60°C to ensure the sol fully coated the particles. The mixture was then centrifuged and dried at 100°C to form a gel layer.

[0080] The dried powder was placed in a tube furnace and heat-treated at 600°C in air for 2 hours to completely transform the precursor into crystalline Y₂O₃. By controlling the sol concentration and the number of impregnations, a dense Y₂O₃ diffusion barrier layer with a thickness of approximately 0.6 μm was obtained.

[0081] Radio frequency magnetron sputtering was employed, using a Fe-20wt%Cr alloy as the target material.

[0082] Y₂O₃-coated powder was placed on a rotatable substrate stage, and the vacuum level was better than 5 × 10⁻⁶. -3 Sputtering was performed under conditions of 0.5 Pa argon working pressure. The RF power was set to 200 W and the deposition time to 60 minutes. A uniform and well-bonded Fe-Cr alloy external functional layer with a thickness of approximately 0.8 μm was deposited on the powder surface.

[0083] The deposited powder was annealed under vacuum at 500°C for 1.5 hours to improve the density of the coating, release stress, and enhance the interfacial bonding between the Y2O3 layer and the Fe-Cr layer, thus obtaining functional particles.

[0084] Preparation Example 4

[0085] Preparation of functionalized particles: Cu-Ni-Sn core / Y2O3 diffusion barrier layer / Fe-Cr-Mo outer functional layer:

[0086] Cu-4wt%Ni-2wt%Sn pre-alloyed spherical powder was prepared using vacuum induction melting combined with gas atomization technology. The powder particle size D50 was controlled at 45±5μm.

[0087] Fluidized bed atomic layer deposition was employed. Tris(ethylcyclopentadienyl)yttrium and water were used as precursors, and the deposition temperature was 300℃.

[0088] By controlling the number of ALD cycles to 500, a uniform, pinhole-free Y2O3 film with a thickness of approximately 0.4 μm was formed by layer-by-layer growth on the surface of the fluidized core powder.

[0089] A combined DC magnetron sputtering and high-power pulsed magnetron sputtering technology was employed. The target material was an Fe-22wt%Cr-3wt%Mo alloy.

[0090] First, a base bonding layer of approximately 0.5 μm was deposited in DC mode at a power of 2 kW. Then, the deposition continued in HiPIMS mode at a peak power of 100 kW and a frequency of 100 Hz until the total thickness reached 1.5 μm.

[0091] The powder was annealed in two steps: first, it was annealed at 400°C under an argon atmosphere for 1 hour, and then annealed at 550°C under vacuum for 0.5 hours to obtain functional particles.

[0092] Example 1

[0093] Matrix steel powder: composition of C 0.30wt.%, Si 0.20wt.%, Mn 0.85wt.%, Cr 1.10wt.%, Mo 0.30wt.%, Ni 1.50wt.%, V 0.10wt.%, Nb 0.05wt.%, B 0.002wt.%, gas atomization powder, D50=75μm.

[0094] In a low-carbon steel cladding, matrix steel powder was uniformly mixed with 8 vol% of the functional particles prepared in Preparation Example 1, and the mixture was filled into the outer ring of the cladding. The radial thickness of the outer ring was 1.0 mm, and the center was filled with pure matrix steel powder. A vacuum of 5 × 10⁻⁶ ppm was applied at 400°C. -3Pa is then sealed with a weld.

[0095] Hot isostatic pressing was performed at 1120℃ / 115 MPa / 3 h to obtain a fully dense φ150 mm composite blank.

[0096] Thermomechanical processing: Heating to 1100℃, holding at that temperature, forging the billet, and then performing multiple drawing operations in the 900-950℃ range, with a cumulative true strain >0.8, and a final forging temperature of 850℃.

[0097] Heat treatment: Austenitizing: Hold at 880℃ for 1.5 h, then oil quench. Tempering: Hold at 500℃ for 3 h, then water quench.

[0098] Machining and surface treatment: Machining into M30 bolts, the surface is only phosphated, and after passing magnetic particle testing, the finished product is obtained.

[0099] Example 2

[0100] The preparation process is the same as in Example 1, except that the functional particles prepared in 8 vol% Preparation Example 1 are replaced with functional particles prepared in 8 vol% Preparation Example 2 to obtain the finished product.

[0101] Example 3

[0102] The preparation process is the same as in Example 1, except that the functional particles prepared in 8 vol% Preparation Example 1 are replaced with functional particles prepared in 8 vol% Preparation Example 3 to obtain the finished product.

[0103] Example 4

[0104] The preparation process is the same as in Example 1, except that the functional particles prepared in 8 vol% Preparation Example 1 are replaced with the functional particles prepared in 8 vol% Preparation Example 4 to obtain the finished product.

[0105] Example 5

[0106] The preparation process is the same as in Example 1, except that the 8 vol% functional particles are replaced with 3 vol% functional particles to obtain the finished product.

[0107] Example 6

[0108] The preparation process is the same as in Example 1, except that the 8 vol% functional particles are replaced with 15 vol% functional particles to obtain the finished product.

[0109] Example 7

[0110] The preparation process is the same as in Example 1, except that the outer ring with a radial thickness of 1.0 mm is replaced with an outer ring with a radial thickness of 0.3 mm to obtain the finished product.

[0111] Example 8

[0112] The preparation process is the same as in Example 1, except that the outer ring with a radial thickness of 1.0 mm is replaced with an outer ring with a radial thickness of 2.0 mm to obtain the finished product.

[0113] Example 9

[0114] Matrix steel powder: composition of C 0.25wt.%, Si 0.1wt.%, Mn 0.4wt.%, Cr 0.7wt.%, Mo 0.15wt.%, Ni 0.8wt.%, gas atomization powder, D50=75μm.

[0115] The preparation process is the same as in Example 1, and the finished product is obtained.

[0116] Example 10

[0117] Matrix steel powder: composition of C 0.38wt.%, Si 0.5wt.%, Mn 1.2wt.%, Cr 1.5wt.%, Mo 0.5wt.%, Ni 2.5wt.%, gas atomization powder, D50=75μm.

[0118] The preparation process is the same as in Example 1, and the finished product is obtained.

[0119] Example 11

[0120] Matrix steel powder: composition of C 0.38wt.%, Si 0.5wt.%, Mn 1.2wt.%, Cr 1.5wt.%, Mo 0.5wt.%, Ni 2.5wt.%, V 0.05wt.%, gas atomization powder, D50=75μm.

[0121] The preparation process is the same as in Example 1, and the finished product is obtained.

[0122] Example 12

[0123] Matrix steel powder: composition of C 0.38wt.%, Si 0.5wt.%, Mn 1.2wt.%, Cr 1.5wt.%, Mo 0.5wt.%, Ni 2.5wt.%, V 0.05wt.%, Nb 0.02wt.%, gas atomization powder, D50=75μm.

[0124] The preparation process is the same as in Example 1, and the finished product is obtained.

[0125] Example 13

[0126] Matrix steel powder: composition of C 0.38wt.%, Si 0.5wt.%, Mn 1.2wt.%, Cr 1.5wt.%, Mo 0.5wt.%, Ni 2.5wt.%, V 0.05wt.%, B 0.0035wt.%, gas atomization powder, D50=75μm.

[0127] The preparation process is the same as in Example 1, and the finished product is obtained.

[0128] Comparative Example 1

[0129] Material: Commercial 42CrMoV steel, with a nominal tensile strength of approximately 1000-1200 MPa.

[0130] Forging and tempering: The φ80 mm bar stock is heated to 850℃ for forging, with a final forging temperature ≥800℃. It is then subjected to tempering treatment: oil quenching at 850℃ + tempering at 580℃.

[0131] Machining: Turning and grinding to the size of M30 bolt blank, then rolling to form threads.

[0132] Surface treatment: Standard hot-dip galvanizing process is adopted, with a coating thickness of about 50-80μm, and passivation and grease coating are performed to obtain the comparative finished product.

[0133] Comparative Example 2

[0134] The matrix steel powder in Example 1 was uniformly mixed with 8 vol% of the core-shell particles prepared in Example 1, and then integrated and vacuum-sealed. The finished product was obtained by HIP, thermomechanical processing, heat treatment, machining and surface treatment in the same manner as in Example 1.

[0135] Comparative Example 3

[0136] In Example 1, the outer ring filling material was replaced with matrix steel powder + 4 vol% elemental Cu powder + 4 vol% Fe-25wt%Cr-5wt%Mo alloy powder, with pure matrix steel powder in the center. The mixture was then vacuumed at 400°C to a density of 5×10⁻⁶. -3 After Pa sealing, the product undergoes the same HIP, thermomechanical processing, heat treatment, machining, and surface treatment as in Example 1 to obtain the comparative finished product.

[0137] Comparative Example 4

[0138] Following the same process as in Preparation Example 1, skipping the sol-gel method for Al2O3, Fe-Cr-Mo alloy layers were directly coated onto the Cu-Ni core using the same fluidized bed sputtering process to obtain Cu-Ni@Fe-Cr-Mo particles.

[0139] Using the same preparation process as in Example 1, the functional particles were replaced with Cu-Ni@Fe-Cr-Mo particles to obtain the comparative finished product.

[0140] Comparative Example 5

[0141] Following the same process as in Preparation Example 1, the Fe-25wt%Cr-5wt%Mo alloy target was replaced with a Fe-5wt%Mo alloy target to prepare Cu-Ni / Al2O3 / Fe-Mo particles.

[0142] Using the same preparation process as in Example 1, the functional particles were replaced with Cu-Ni / Al2O3 / Fe-Mo particles to obtain the comparative finished product.

[0143] Comparative Example 6

[0144] The preparation process is the same as in Example 1, but after hot isostatic pressing, the thermomechanical processing is replaced by a light upsetting on a press with a reduction of 5-8 mm, to obtain the comparative finished product.

[0145] Performance testing:

[0146] The following performance tests were performed on the finished products prepared in Examples 1, 5, and 6 above, as well as Comparative Examples 1-6:

[0147] The tensile strength and yield strength of the materials prepared in Examples 1, 5 and 6 and Comparative Examples 1-6 were tested according to GB / T 228.1-2021 "Metallic materials - Tensile testing - Part 1: Test method at room temperature". The specific results are shown in Table 1.

[0148] The impact toughness of the materials prepared in Examples 1, 5, and 6, as well as Comparative Examples 1-6, was tested according to GB / T 229-2020 "Metallic Materials Charpy Pendulum Impact Test Method". The specific results are shown in Table 1.

[0149] Salt spray corrosion tests were conducted on the materials prepared in Examples 1, 5, and 6, as well as Comparative Examples 1-6, according to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test". The specific results are shown in Table 1.

[0150] According to GB / T 17899-2023 "Corrosion of Metals and Alloys - Potentiodynamic Measurement Method of Pitting Potential of Stainless Steel in Sodium Chloride Solution", the pitting potential of the materials prepared in Examples 1, 5 and 6 and Comparative Examples 1-6 was tested, and the specific results are shown in Table 1.

[0151] Referring to ASTM G5, "Standard Reference Test Method for Making Potentiodynamic Anodic Polarization Measurements", the current-time curves under constant potential were monitored after scratching to evaluate the current decay behavior. The scratch repassivation capability of the materials prepared in Examples 1, 5, and 6, as well as Comparative Examples 1-6, was tested, and the specific results are shown in Table 1.

[0152] Table 1

[0153]

[0154] As can be seen from the performance data in Table 1, Embodiments 1, 5 and 6 of the present invention achieve synergistic improvement in mechanical properties and corrosion protection performance by adjusting the volume fraction of functional particles and combining them with an optimized dual-network structure design. Among them, Embodiment 6 exhibits the best comprehensive protection performance and high strength, while Embodiment 5 has the best toughness reserve while ensuring high corrosion resistance.

[0155] Examples 1, 5, and 6 show the nonlinear effect of functional particle content on performance, wherein:

[0156] Example 1 constructed an ideal dual network of ion-release and sacrificial anode, achieving the best balance of strength, toughness and corrosion resistance.

[0157] Example 5: The reduced proportion of low-content functional particles led to a decrease in the density of microanodes and ion sources, but the positive contribution of the sacrificial anode effect to the strength was weakened.

[0158] Example 6: High-density functional particles constructed an extremely well-developed self-passivation-slow-release dual network. The extremely high ion concentration and current discharge channels significantly increased the threshold for matrix dissolution, causing the pitting potential to soar to the highest level in the field at +0.88 V. Furthermore, sufficient repair ions shortened the scratch repassivation time to 15 min. However, the excessively high particle volume fraction disrupted the continuity of the matrix, leading to increased stress concentration and a significant deterioration in impact toughness to 38 J.

[0159] The comparison between Comparative Example 1 and Example 1 shows that the zinc plating layer forms an galvanic corrosion with the substrate. After the zinc plating layer is depleted, there is no effective protection inside. The material is in a continuous active state. The scratch repassivation time is "unrepairable". In addition, the substrate is affected by the corrosion of the large cathode and small anode, and the strength and toughness are greatly reduced.

[0160] As can be seen from the comparison between Comparative Example 2 and Example 1, although Comparative Example 2 has a core-shell structure, it lacks spatial connectivity. Ion transport is limited by Fick diffusion, resulting in slow repair. Furthermore, the uniformly distributed particles rupture the matrix, and the impact energy at -40°C is only 45J.

[0161] The comparison between Comparative Example 3 and Example 1 shows that the lack of core-shell protection led to premature oxidation and failure of the particles, and the elemental particles exacerbated electrochemical corrosion, with the time to red rust appearing plummeting to 1000 h and the pitting potential being only +0.45 V. The 180 min repassivation time indicates that it has almost lost its active repair capability.

[0162] As can be seen from the comparison between Comparative Example 4 and Example 1, core-shell interdiffusion leads to blockage of the slow-release channel, resulting in intermittent ion release and weak corrosion protection.

[0163] The comparison between Comparative Example 5 and Example 1 shows that the lack of Cr element prevents the formation of a dense passivation film, and the abnormal electrochemical activity of the outer functional layer leads to an accelerated corrosion rate. The 200 min repassivation time indicates that the repair process is extremely slow.

[0164] A comparison of Comparative Example 6 and Example 1 shows that by applying thermomechanical processing with a cumulative true strain ≥ 0.6, the functional particles are significantly elongated along the forging / rolling flow lines, forming chain-like, lamellar, or discontinuous network distributions, thereby constructing a continuous corrosion control network near the surface. This network not only provides self-passivation capability through the Cr-rich outer functional layer, but also achieves active repair function by releasing corrosion-inhibiting ions at localized damage sites through the Cu-based core. Simultaneously, this corrosion control network and the mechanical load-bearing network composed of the base steel interpenetrate three-dimensionally and synergistically within the near-surface depth range, jointly forming a self-passivation-slow-release dual-network structure. This dual-network architecture achieves spatial division of labor and performance coupling between load-bearing strengthening and active corrosion protection functions, thereby significantly improving its pitting corrosion resistance and scratch self-repair efficiency while ensuring a material Rm ≥ 1250 MPa, ultimately achieving synergistic optimization of mechanical properties and corrosion protection performance.

[0165] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present application in any way. Although the present application has been disclosed above with reference to preferred embodiments, it is not intended to limit the present application. For those skilled in the art, it will be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-load bolt steel with self-passivation function, wherein the high-load bolt steel is a bar or forging, characterized in that, Including the cardiac basal region and the near-surface functional complex region; The core matrix region is formed of matrix steel, which is a Cr-Mo-Ni quenched and tempered steel capable of achieving Rm≥1200 MPa, and its microstructure is mainly composed of tempered martensite or tempered sorbite. The near-surface functional composite zone is located within a depth of 0.3–2.0 mm radially inward from the outer surface of the bolt steel, and covers / surrounds the outer periphery of the core matrix zone. The near-surface functional composite zone is composed of a continuous steel skeleton made of the matrix steel and functional particles dispersed within the skeleton. The volume fraction of the functional particles in the near-surface functional composite zone is 3–15 vol%. The functional particles are elongated along the forging / rolling flow line direction in the near-surface functional composite zone, with an aspect ratio greater than 2:1, forming a chain-like / lamellar / discontinuous network distribution, constituting a corrosion control network. The corrosion control network is nested with the continuous steel skeleton and forms a three-dimensional interpenetrating self-passivation-slow-release dual network structure in the near-surface functional composite zone. The functional particle has a core-shell structure, wherein the core of the core-shell structure is composed of Cu or a Cu-based alloy, and the shell of the core-shell structure includes a diffusion barrier layer and an outer functional layer arranged sequentially from the inside to the outside. The diffusion barrier layer is made of one or more of Al2O3, Y2O3, or TiC; the outer functional layer is made of a Cr-rich alloy or a Cr-rich-Mo alloy, wherein the Cr content is ≥15 wt%.

2. The high-load bolt steel with self-passivation function according to claim 1, characterized in that, The base steel comprises, by weight percentage: C 0.25%–0.38%, Si 0.10%–0.50%, Mn 0.50%–1.20%, Cr 0.70%–1.50%, Mo 0.15%–0.50%, Ni 0.80%–2.50%, with the balance being Fe and unavoidable impurities.

3. The high-load bolt steel with self-passivation function according to claim 2, characterized in that, The base steel also contains one or more of the following elements: V 0.05%–0.15%, Nb 0.02%–0.10%, and B 0.0005%–0.0035%.

4. The high-load bolt steel with self-passivation function according to claim 1, characterized in that, The overall equivalent diameter D90 of the functional particles is ≤80μm, and the functional particles are distributed in a discontinuous network-like permeation tendency within the near-surface functional composite zone.

5. The high-load bolt steel with self-passivation function according to claim 4, characterized in that, The core of the functional particle is a Cu-Ni alloy, Cu-Sn alloy, or Cu-Ni-Sn alloy, wherein the total content of Ni and Sn is ≤15 wt%.

6. The high-load bolt steel with self-passivation function according to claim 4, characterized in that, The thickness of the diffusion barrier layer is 0.1-2.0 μm, the thickness of the outer functional layer is 0.3-2.0 μm, and the content of Cr in the outer functional layer is 15-30 wt%, and the content of Mo is 1-5 wt%.

7. The high-load bolt steel with self-passivation function according to claim 4, characterized in that, The outer functional layer comprises Fe-Cr or Fe-Cr-Mo, wherein Cr is 15-30 wt% and Mo is 1-5 wt%, and is metallurgically bonded to the base steel in a nanocrystalline / microcrystalline morphology.

8. A process for preparing high-load bolt steel with self-passivation function as described in any one of claims 1-7, characterized in that the following... step: (1) Raw material preparation: Provide matrix steel powder and core-shell structure functional particles, wherein the functional particles meet the requirements of any one of claims 1, 4-7; (2) Gradient powder loading and encapsulation: Within a low-carbon steel casing, a near-surface powder loading zone is formed using a mixture of the matrix steel powder and 3-15 vol% of the functional particles, while a core powder loading zone is formed using pure matrix steel powder; the mixture is then heated at 400-450℃ for degassing, followed by heating at 350-500℃ and vacuuming to ≤10 -2 After sealing (Pa); (3) Hot isostatic pressing (HIP) densification: Hold pressure at 1090-1120℃ and 100-120 MPa for 2-5 h, then cool to obtain a fully dense gradient composite preform; (4) Thermomechanical deformation: The gradient composite billet is heated to 1080-1140℃ and held at that temperature. After holding at that temperature with an effective cross section of 0.6-1.2 min / mm, it is forged. At least two passes of deformation are performed in the temperature range of 850-960℃, with a single pass reduction of 15-30%, a cumulative true strain ≥0.6, and a final forging temperature ≥820℃. After forging, the billet is slowly cooled or put into the furnace. (5) Heat treatment: Austenitizing quenching and tempering are performed sequentially; the austenitizing quenching temperature is 860-900℃, and the holding time is 2-5 h; the tempering temperature is 480-520℃, and the holding time is 2-5 h, followed by air cooling or water cooling. (6) Machining and surface treatment: Turn / grind to bolt size, roll forming of threads, low temperature stabilization: 150-220℃×1-3 h dehydrogenation baking, phosphating or chromium-free passivation treatment of the surface to obtain finished bolts / studs / anchors; (7) Inspection: Magnetic particle testing or eddy current testing is performed on the root of the finished thread to remove unqualified products.

9. The preparation process according to claim 8, characterized in that, In step (1), the core-shell structured functional particles are prepared by a method comprising the following steps: (a) Provide Cu-based alloy core powder with a particle size D50 of 20-80 μm; (b) An Al2O3 or Y2O3 diffusion barrier layer with a thickness of 0.2-1.5 μm is formed on the surface of the core powder using the sol-gel method or chemical vapor deposition method; (c) An Fe-Cr-Mo alloy external functional layer with a thickness of 0.3-2.0 μm is deposited on the surface of the diffusion barrier layer by magnetron sputtering or fluidized bed chemical vapor deposition, wherein the Cr content is 15-30 wt% and the Mo content is 1-5 wt%. (d) The coated powder is heat-treated at 400-600℃ for 0.5-2 hours in an inert or vacuum atmosphere to obtain functional particles.

10. A high-load fastener, characterized in that, The high-load bolt steel according to any one of claims 1-7 is processed to have a nominal tensile strength grade ≥10.9.

Citation Information

Patent Citations

  • Delayed-fracture-resistant high-strength bolt steel material and bolt manufacturing method

    CN117467896A